Evaluation of simplified oral hygiene index of the elementary school students before fluoride mouthwash - doi: 10.4025/actascihealthsci.v35i2.13205 (Acta Scientiarum. Health Sciences, 2013)
The State Program of fluoride mouthwashes for caries control was established in 1980 in elementary schools of Paraná State covering children 7-11 years old. Knowing the importance of removing bacterial plaque to reach the maximum desired effect of prevention, this study aimed to evaluate the Simplified Oral Hygiene Index, before applying the solution of Sodium Fluoride (NaF; 0.2%) in children from an elementary school in the city of Nova Aurora, Paraná State, by using disclosing dental plaque. This is a quantitative research, descriptive and exploratory whose data were obtained through a specific form, with 61 children and analyzed using descriptive statistics with distribution of absolute and percentage frequencies. Most children (60%) showed the worst results - regular and bad - with presence of plaque and risk of dental caries. Therefore, we should establish a prevention program in oral health that must involve parents and students. This program should be developed by health professionals inside the school, explaining about the etiologic factors, causes and consequences of plaque, the techniques of cleaning and maintenance of hygiene instruments, and the risks of the lack of proper hygiene in the oral cavity.